Support needs assessment tool for people with disability wanting to participate in sport and exercise (SNAT-SE): Usability and acceptability testingKey points: - Jessica Hill; Kelly Clanchy; Stewart Trost; Jennifer Fleming; Emma Beckman; Sean Tweedy; Iain Dutia; Sjaan Gomersall (JSAMS Plus)
Background: People with disability participate in sport and exercise at lower rates than the general population. Health and fitness professionals’ lack of knowledge regarding the support needs of people with disability has been identified as a major barrier to participation. To address this barrier, we developed a support needs assessment tool for people with disability wanting to participate in sport and exercise. The present study explored the usability and acceptability of the tool from the perspectives of the end-users. Method: An online survey was used to gather data on the usability and acceptability of the tool from the perspectives of people with disability, health professionals, community-based fitness professionals, and relevant researchers. Results: A total of 52 people completed the survey. Participants reported that the SNAT-SE was a useful and acceptable tool to assess the support needs of people with disability wanting to participate in sport and exercise. Participants also provided recommendations on refinements to further enhance the use of the tool. Refinements included increased clarity of the language used throughout the tool, a reduction in the overall length and flexibility in administration to reduce the time burden, and modifications to ensure all disability populations could equally benefit from the tool. Conclusion: Overall, the tool showed good usability and acceptability. Further research is required to evaluate the tool's effectiveness in improving the confidence and quality of service delivery of health and fitness professionals supporting people with disability to participate in sport and exercise.